Modal content measurements (S2) of negative curvature hollow-core photonic crystal fibers - Bock, V.; Ploetner, M.; De Vries, O.; Nold, J.; Haarlammert, N.; Schreiber, Thomas; Eberhardt, R.; Tuennermann, A. (Optics Express, 2017)
We present modal content measurements (S2) of two different negative curvature hollow-core photonic crystal fibers: a kagome fiber and an ice cream cone fiber. Their sensitivity towards mode matching, bending and polarization is analyzed. For the kagome fiber, a higher order mode suppression of 17dB under optimal conditions was achieved, and for the ice cream cone fiber there was a suppression of up to 42dB. Polarization turned out to be a critical parameter for good higher order mode suppression in both fibers.
CRIS-Team Scopus Importer:2023-04-20